2015
DOI: 10.1155/2015/307879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factor VIII as a Risk Factor in Indian Patients with DVT

Abstract: Introduction. Elevated factor VIII population in the Indian population has not been studied as a possible risk factor for deep vein thrombosis (DVT). High factor VIII level is considered a predisposing factor for DVT and its recurrence. However it is known to vary between populations and its exact role in the etiopathogenesis of thrombophilia remains unknown. Material and Methods. Factor VIII levels of patients with DVT who had undergone a prothrombotic workup as a part of their workup was compared to normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, there are insufficient data in comparison with Indian population. Two studies from India have shown that the mean factor VIII and VWF values are higher in blood donors in India when compared to other populations around the world 26,27 . Although the exact mechanism for this is uncertain, this could explain the higher values seen among the OCs of our study.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, there are insufficient data in comparison with Indian population. Two studies from India have shown that the mean factor VIII and VWF values are higher in blood donors in India when compared to other populations around the world 26,27 . Although the exact mechanism for this is uncertain, this could explain the higher values seen among the OCs of our study.…”
Section: Discussionmentioning
confidence: 57%
“…Two studies from India have shown that the mean factor VIII and VWF values are higher in blood donors in India when compared to other populations around the world. 26,27 Although the exact mechanism A variable laboratory phenotype was seen among the OCs.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have claimed that non-O blood types have the risk of thrombosis and O blood type with the risk of hemorrhage. 4,6,8,[10][11][12] Factor-VIII is an acute phase protein and is increased temporarily during an inflammatory process. Kamphuisen's study showed no relationship between factor VIII activity and CRP (C-Reactive Protein) in venous thrombosis patients.…”
Section: Introductionmentioning
confidence: 99%